Sejarah dan Fiksi dalam Dua Novel Karya Kwee Tek Hoay: - Irna Gayatri D. Ardiansyah (Kantor Bahasa Provinsi Maluku Utara, 2015)
This research aims at analyzing the history and fiction in two novels by Kwee Tek Hoay. The researcher searches for some information from library and website resources to support this research. Specifically, the researcher searches for library resources containing information about the literature of Chinese Malay. The researcher analyzes Atsal Mulahnya Timbul Pergerakan Tionghoa and Berkahnya Malaise by using qualitative method. Bassically, the two novels present the history,i.e. Malaise event on Berkahnya Malaise and the origin of Hwee Koan community movement on Atsal Mulahnya Timbul Pergerakan Tionghoa. However, there is afiction appeared from author’s idea on the two novels. The idea comes in the form of communication presented between literature and the readers.